Randomized Trial Evaluating Targeted Photographic Health Communication Messages in Three Stigmatized Populations: Physically-Disabled, Senior, and Overweight/Obese Individuals. Issue 10 (2nd November 2018) - Buller, Mary K.; Andersen, Peter A.; Bettinghaus, Erwin P.; Liu, Xia; Slater, Michael D.; Henry, Kimberly; Fluharty, Lyndsay; Fullmer, Steven; Buller, David B.
Abstract : The homophily principle that perceived similarities among people produce positive reactions is a cross-cultural, global phenomenon. The prediction that photographs depicting models similar to the target population improve health communication was tested. Three nationally-representative samples (n = 1, 796) of adults who are disabled, seniors, or considered overweight/obese were selected from GfK's Knowledge Panel®. Participants read a message promoting physical activity and improved diets and responded to assessments of behavioral intentions, outcome and self-efficacy expectations, and identification. Photographs from a stock photograph service versus photographs created for the research project to match the three populations, Real Health Photos ( RHP ), were included in the message. Structural equation modeling confirmed that RHP which matched the population increased behavioral intentions mediated by identification (p < 0.05) in the physically-disabled and overweight/obese samples. Messages with only half of the matched RHP images had these same positive indirect effects (p < 0.05). Matched visual images in health messages improved effectiveness by capitalizing on the homophily and identification processes. Health educators should leverage these hardwired, evolutionary, biological phenomena that extend to health status as well as race and ethnicity. For optimal effects, not all persons shown need to be homophilous to the target audience, reducing logistical difficulties in showing diverse persons of various types.